In silico ADMET prediction, evaluation of cytotoxicity in mouse splenocytes and preliminary evaluation of in vitro antimalarial activity of 4-(4-chlorophenyl) thiazole compounds - DA SILVA, Beatriz R.M.G. (2023)
Funding Information: This study was funded by the Brazilian agencies Fundação de Amparo à Pesquisa do Estado de Pernambuco-FACEPE (Process APQ-0498-4.03/19) and researcher fixation grant-FACEPE (Process BFP-0038-04.03/21). Thanks to MR4, who provided us with the P. falciparum MRA-1029 strain provided by Andrew Talman, Robert Sinden that we used in the trials. The work was partially supported by the FCT project reference CIRCNA/BRB/0281/2019_AMAZING and GHTM-UID/Multi/04413/2013. Funding Information: This study was funded by the Brazilian agencies Fundação de Amparo à Pesquisa do Estado de Pernambuco - FACEPE (Process APQ-0498-4.03/19) and researcher fixation grant -FACEPE (Process BFP -0038-04.03/21). Thanks to MR4, who provided us with the P. falciparum MRA-1029 strain provided by Andrew Talman, Robert Sinden that we used in the trials. The work was partially supported by the FCT project reference CIRCNA/BRB/0281/2019_AMAZING and GHTM-UID/Multi/04413/2013. Publisher Copyright: © 2023, Academia Brasileira de Ciencias. All rights reserved.